Weed dynamics and yield of wheat under stale seedbed technology with an additional tillage - Yonas, Muhammad Waqas; Mubeen, Khuram; Aziz, Mudassir; Ahmed, Wazir; Ghaffar, Abdul; Alam, Mehmood; Ahmad, Matlob; Khaliq, Abdul; Qayyum, M. Abdul; Abbas, M. Bilal (Journal of Pure and Applied Agriculture, 2023)
A field study was undertaken to investigate the influence of stale seedbed on weed dynamics and yield performance of wheat at farm area, MNS-University of Agriculture Multan. Current study was carried out under RCBD with three replications. This experiment have eight treatments viz: one till + no herbicide, one till + glyphosate 48% SL at 711 a.i mL/ha, one till + paraquat 20% SL at 494 a.i mL/ha, one till + atlantis (mesosulfuron-methyl and iodosulfuron-methyl sodium) 6% WG at 15 a.i g/ha, one till + glyphosate at 48% SL 356 a.i mL/ha + paraquat 20% SL at 247 a.i mL/ha, one till + glyphosate 48% SL at 356 a.i mL/ha followed by atlantis 6% WG at 7.5 a.i g/ha, one till + paraquat 20% SL at 247 a.i mL/ha followed by atlantis 6% WG at 7.5 a.i g/ha, one till + glyphosate 48%